Zinsomnia: online application test of insomnia disorder among students - Ruslan, Nur Zafira Amani; Abdul Aziz, Azlan; Zulkifli, Zuhri Arafah (College of Computing, Informatics, and Mathematics, 2025)
Insomnia is a sleep disorder that negatively impacts a student's academic achievement, physical health, mental well-being, and overall quality of life. In addition, it also impairs critical thinking, problem-solving skills and can lead to hindering academic success among students. Such occurrence is due to insomniac individuals are unaware of their condition. The trepidation relating to acquiring treatment also poses a hindrance to these insomniac individuals. The purpose of this study is to design a mobile application about Insomnia disorder initial treatment addressing the problems on awareness and the distress related insomnia. The project implemented the Waterfall methodology and utilized the usability evaluation with a 5-point Likert scale as a data collection method.